2020
DOI: 10.1371/journal.pone.0244546
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the use of patient-reported data by health care insurers: A scoping review

Abstract: Background Patient-reported data are widely used for many purposes by different actors within a health system. However, little is known about the use of such data by health insurers. Our study aims to map the evidence on the use of patient-reported data by health insurers; to explore how collected patient-reported data are utilized; and to elucidate the motives of why patient-reported data are collected by health insurers. Methods The study design is that of a scoping review. In total, 11 databases were sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This information will support decision making on whether treatments should be reimbursed in health insurance plans. However, health insurers lack interest in PROs and outcome-driven payment [ 41 , 42 ]. Transparency on which treatments provide the highest value for patients becomes increasingly important especially in patients with MM, owing to the introduction of expensive new and prolonged treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This information will support decision making on whether treatments should be reimbursed in health insurance plans. However, health insurers lack interest in PROs and outcome-driven payment [ 41 , 42 ]. Transparency on which treatments provide the highest value for patients becomes increasingly important especially in patients with MM, owing to the introduction of expensive new and prolonged treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The current health information landscape is not sufficiently robust to support healthcare insurers in operationalizing care procurement policies anchored in people-centred value-based principles. Aside from the healthcare insurers’ poor availability of care quality and outcome data (notably, PROMs and PREMs) [ 12 ], unclear regulation about data custodianship hampers a greater use of intelligence towards supporting value creation. It is not clear which data each actor in the system should have access to and what the value chain of data could be like.…”
Section: Discussionmentioning
confidence: 99%
“…The meeting was structured in two parts. First, to contextualize the study, ÓBF shared conclusions of the scoping review performed earlier by members of this research group on the use of patient-reported data by healthcare insurers [ 12 ]. Secondly, NK moderated the discussion around four discussion statements drawn from phase 1 of the study (these were displayed in both English and Dutch) while ÓBF, VB, and DK took notes (Additional file 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations